PERAN KOMUNITAS PKUVIDGRAM DALAM MENINGKATKAN KREATIFITAS PENGGUNA INSTAGRAM DI KOTA PEKANBARU - Kurniawan, Muhammad Dicky; Jalil, Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The study concluded the problems that will be used as the discussion, namely (1) How the profile of the community of Pkuvidgram, (2) what are the advantages that users get on Instagram after joining the community, (3) any Activity Pkuvidgram community perpetrated in enhancing creativity in the city of Pekanbaru instagram users. This research aims to know the profile of the community Pkuvidgram that exist in the city of Pekanbaru. To find out what activities are conducted community Pkuvidgram against user creativity instagram in Pekanbaru. Instagram has become the lifestyle of the community of Pkuvidgram, seen from the use of the more instagram leads to the symptoms that indicate the use of media as a personal branding instagram users not content to establish communication create a unique phenomenon. to its users, this application is a container to pour everything that nature diary for each user instagram, Instagram as a container to pour all that in mind, kegembiraa, nervousness and creativity for consumer demand, Here's what mejadikan instagram is a lifestyle for modern society. The role of the community of Pkuvidgram aims to develop the creativity of users as active instragram in making video entertaining and educational, not only that, this community also makes some form of activities such as workshops, meet and greet , and some challenge to lure active users Instagram in developing their creativity, then anyone whose most creative and most of his work will be on the repost or uploaded in your account owned Pkuvidgram, Instagram some those who are good are invited to join the community, than this is the users Instagram channeling his creativity.Key Words: The Role Of The Community Of Pkuvidgram, Improving Creativity